Integration of multiple intelligences theory by form four ESL secondary school teachers in Malaysia - Sarjit Singh, Senam Kaur (2015)
The Multiple Intelligences theory is stipulated in the Curriculum Specification of the New Integrated Secondary School Curriculum as it advocates personalized learning because it takes into consideration the varying human intelligences and all the combinations of intelligences. Hence, by having lessons that catered to the students’ differing combinations and levels of intelligences, teachers will be able to reach individual students and help them hone their dominant intelligences and at the same time strengthen the weaker intelligences. The purpose of the study was to explore and describe the integration of the Multiple Intelligences theory by Form Four ESL Secondary School teachers. The study was guided by three research questions: (1) Is the Multiple Intelligences theory reflected in the teachers’ English as a Second Language lessons? (2) What are the most frequently used intelligences in the English as a Second Language classroom? (3) What are the challenges of integrating the Multiple Intelligences theory in the English as a Second Language classroom? Three Form Four ESL teachers were purposefully selected to participate in this study. The participants were trained secondary school teachers teaching in a day school in Cameron Highlands, Pahang. The study employed a qualitative methodology and the data were collected through a Multiple Intelligences Checklist, interviews and classroom observations to obtain the teachers’ perceptions, experiences and practices related to the study. 5 principles derived from the literature review were used as a guide to explore the integration of the Multiple Intelligences theory in these teachers’ classrooms. They were (1) recognizing the multiple intelligences in teachers and students, (2) integrating multiple intelligences in the lesson, (3) providing opportunities to use multiple intelligences, (4) assessments that enable students to use their multiple intelligences to portray their understanding of the lesson instead of the paper-and-pencil test, (5) encourage apprenticeship to enable students to master a valued skill gradually under the tutelage of a professional. The study revealed that (1) two of the teachers recognized their students’ multiple intelligences aptly, (2) students’ multiple intelligences were engaged especially during the set-induction but the verbal-linguistic and logical-mathematical intelligences were dominantly used during the while and post-learning stage as the teachers were bound to the text book, (3) only one teacher provided her students opportunities to use their multiple intelligences for student projects, (4) drama was used as a multiple intelligences assessment by one teacher, and (5) all three teachers used apprenticeship to enhance their students’ multiple intelligences. Based on these findings, recommendations for the integration of the Multiple Intelligences theory and further studies are provided.